2020
DOI: 10.1055/a-1185-9283
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of Long Non-Coding RNA ANRIL Suppresses Mouse Mesangial Cell Proliferation, Fibrosis, Inflammation via Regulating Wnt/β-Catenin and MEK/ERK Pathways in Diabetic Nephropathy

Abstract: Aims Our study aimed to investigate the role of long non-coding RNA ANRIL (lnc-ANRIL) knock-down in regulating cell activities, inflammation and downstream signaling pathways in mouse mesangial cellular diabetic nephropathy (DN) model. Methods The mouse mesangial cells (SV40-MES13 cells) were treated with high-glucose (HG) to construct cellular DN model. Lnc-ANRIL knock-down plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Cerebral ischemia and ischemia-reperfusion injury cause an inflammatory cascade reaction, including inflammatory cell infiltration, release of toxic inflammatory mediators and oxidative stress and excitotoxicity, thus leading to further nerve tissue damage and cell death (13). Over recent years, multiple studies have reported that anril regulates the inflammatory response and proliferation of cells through different signaling pathways in pathological aspects of ischemic stroke (14)(15)(16). For example, Zhao reported that lncRNA ANRIL knockdown improves cerebral infarction-induced neurological deficits and decreases the number of apoptotic neurons in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia and ischemia-reperfusion injury cause an inflammatory cascade reaction, including inflammatory cell infiltration, release of toxic inflammatory mediators and oxidative stress and excitotoxicity, thus leading to further nerve tissue damage and cell death (13). Over recent years, multiple studies have reported that anril regulates the inflammatory response and proliferation of cells through different signaling pathways in pathological aspects of ischemic stroke (14)(15)(16). For example, Zhao reported that lncRNA ANRIL knockdown improves cerebral infarction-induced neurological deficits and decreases the number of apoptotic neurons in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“… 86 Similarly, lncRNA ANRIL knockdown can suppress mouse mesangial cell proliferation, inflammation and fibrosis via ERK pathways in a diabetic nephropathy model. 148 Akt also participates in inhibiting cell apoptosis and reducing eNOS expression via the ERK pathway in a bilateral common carotid occlusion model. 149 …”
Section: Significant Role Of Long Noncoding Rnas In Cerebral Ischemiamentioning
confidence: 98%
“…Monocyte chemotactic protein 1 (MCP-1) belongs to a small cytokine of the CC chemokine family, which has been identified as an important proinflammatory cytokine secreted by monocytes, macrophages, fibroblasts, vascular endothelial cells, B cells, and smooth muscle cells during an inflammatory response. Moreover, MCP-1 has specific chemotactic activation on monocytes/macrophages [8][9][10]. Accordingly, the present study investigated the prognostic value of the combined assay of IL-6, NF-κB, and MCP-1 in diabetic nephropathy to provide a reference for future clinical practice.…”
Section: Introductionmentioning
confidence: 98%